Pelatihan Metode Systematic Literature Review (SLR) dan Meta-Analysis dalam Pengolahan Data Penelitian pada Mahasiswa Sarjana Ilmu Kesehatan Masyarakat Universitas Cenderawasih - Ilmidin Ilmidin; Arisjulyanto, Dedy; Suharmanto Suharmanto; Kusuma, Ardhanari Hendra (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
A Systematic Literature Review (SLR), also referred to as a literature review, serves as a foundation for the development of scientific knowledge, policymaking, practice, and guidelines that are firmly grounded in evidence-based research. Meta-analysis is often regarded as a more advanced and focused component within the broader scope of SLR. The authors observed that many students still rely predominantly on descriptive research methods that focus solely on frequencies, without conducting in-depth observation or analysis of variables. The purpose of this community service activity (PKM) is to conduct training for students on a more advanced methodological approach meta-analysis. The training is scheduled for two days: the first day focuses on theoretical concepts, and the second day is dedicated to hands-on practice. To evaluate the effectiveness of the training, identical pre- and post-training questionnaires will be distributed to all participants. The results demonstrate that this activity effectively enhances students’ understanding of SLR and meta-analysis through practical application using appropriate software tools. The implementation of pre- and post-tests is crucial for evaluating the success of any educational intervention.